Al-Jarḥ Wa Al-Ta’dīl - M. Isa H. A. Salam (Refleksi: Jurnal Kajian Agama dan Filsafat, 2002)
Throughout history, ḥadīth has undergone periods of falsification due to various factors such as political interests, racial discrimination, and ideological motives. During these times, the authentic sayings of the Prophet Muhammad (SAW) were mixed with fabricated statements from individuals driven by personal interests. This posed a significant threat to the integrity of Islamic teachings in matters of creed (ʿaqīdah), worship (ʿibādah), and social transactions (muʿāmalah), as ḥadīth is considered a fundamental source of Islamic law. In response, scholars undertook rigorous efforts to authenticate ḥadīth by establishing systematic methodologies to distinguish between authentic and weak reports. One of the primary methods developed was al-Jarḥ wa al-Taʿdīl, a critical science used to evaluate the reliability of ḥadīth narrators. Scholars analyzed the sanad (chain of transmission) and matan (text) of ḥadīth, ensuring that narrators were trustworthy and their transmission was continuous and accurate. Through Jarḥ wa Taʿdīl, scholars assessed the credibility of narrators and determined whether their narrations should be accepted or rejected. This paper discusses the definition, scope, historical development, and key works related to al-Jarḥ wa al-Taʿdīl, highlighting its crucial role in the authentication of ḥadīth.